Myotonia congenita (Thomsen’s disease): (a case report) - Baytok, Vildan (The Turkish Journal of Pediatrics, 1968)
A case of myotonia congenita is presented. The picture was that of myotonia congenita with widespread muscle hypertrophy and widespread myotonia. There was no wasting or weakness and no gonadal atrophy. There were no lenticular opacities, the skull was normal and the E.M.G. showed typical myotonic bursts.